(untitled) (Rajshahi University Journal of Science and Engineering, 2016)
Feasibility for the future electronic devices a thorough investigation on Silicon nanocrystals (Si-NCs) rich Lanthanum Fluoride (LaF3) film fabricated using a novel onestep chemical method has been reported here. Colloidal solution of Si-NCs in hydrofluoric acid (HF) was prepared from meso-porous silicon by ultrasonic vibration (sonication). On a silicon (Si) substrate LaCl3 solution in HCL is allowed to react with the colloidal solution of prepared Si-NCs. LaCl3 reacts with HF of Si-NCs solution and produces LaF3 crystals that deposits on the silicon substrate as a film embedding Si-NCs. This is a novel single step chemical way of depositing LaF3 insulating layer embedding Si-NCs (LaF3:Si-NCs). The XRD and EDX analysis of the deposited film show a polycrystalline and non-stoichiometric nature of LaF3. The presence of Si-NCs was confirmed by SEM. Application of this material has been tested for low-voltage operating non-volatile memory (NVM) and Schottky junction solar cells. The Al/LaF3:Si-NCs/Al structure as NVM offered a memory window of 525 mV at a programming and erasing bias of 2V. LaF3:Si-NCs films showed strong light absorption. Current-Voltage (I-V) characteristics of the Schottky device in ITO/LaF3:Si-NCs/Al structure showed a dependency on the incident light intensity where current was varied in the range of 5 mA to 40 mA and under various light illumination i.e., 400 lux to 1200 lux. Experimental results show a lot of promise of Si-NCs-rich LaF3 film to be used as an insulating film in non-volatile memory as well as a photoactive material in Schottkey junction solar cell.